2005
DOI: 10.1080/17450390512331342395
|View full text |Cite
|
Sign up to set email alerts
|

Ileal and total tract nutrient digestibility in blue foxes (Alopex lagopus) fed extruded diets containing different protein sources

Abstract: This study compared apparent ileal and total tract digestibility of macronutrients and amino acids in blue foxes (Alopex lagopus) fed dry extruded diets. The control diet contained fish meal as the main protein source, while in the other diets 50% of the fish meal protein was replaced by not de-hulled solvent-extracted soybean meal, meat meal or bacterial protein meal. Ileal digestibility was obtained with animals modified with ileorectal anastomosis (IRA method). There were no significant differences in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
8
10
0
Order By: Relevance
“…Moreover, threonine and tryptophan also had relatively low digestibility coefficients to the end of the small intestine regardless of the diet. Similar results were also noted previously in experiments on foxes (6)(7)(8)18), mink (5), and dogs (19,20). In all the diets examined in the present study, TEAA had higher ileal digestibility coefficients compared to TNEAA, which confirms results obtained earlier in foxes (7,8) and dogs (19,20).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, threonine and tryptophan also had relatively low digestibility coefficients to the end of the small intestine regardless of the diet. Similar results were also noted previously in experiments on foxes (6)(7)(8)18), mink (5), and dogs (19,20). In all the diets examined in the present study, TEAA had higher ileal digestibility coefficients compared to TNEAA, which confirms results obtained earlier in foxes (7,8) and dogs (19,20).…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were also noted previously in experiments on foxes (6)(7)(8)18), mink (5), and dogs (19,20). In all the diets examined in the present study, TEAA had higher ileal digestibility coefficients compared to TNEAA, which confirms results obtained earlier in foxes (7,8) and dogs (19,20). This could result from the fact that protein of endogenous origin is not digested as rapidly as dietary protein (5,8).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Ahlstrom et al (2000) and Vhile et al (2005b) also observed lower protein digestibility for diets containing meat meal. The digestibility coefficient of protein contained in standard mixed feed for foxes ranges from 78 to 86%, and usually exceeds 80% (Dahlman et al, 2002;Ahlstrom et al, 2003;Vhile et al, 2005b). …”
Section: Resultsmentioning
confidence: 97%